Nutritional Quality and Yield Performance of Plum (Prunus domestica) Varieties Grown in Punjab, Pakistan - Ahmad, Noman; Ahmad, Sarfraz; Tariq, Iqra; Ali, Iftikhar; Usman, Muhammad; Tariq, Humna; Murtaza, Ghulam; Ahmad, Abrar (BioScientific Review, 2023)
Pakistan is ranked 17th in the world for plum production, with a total output of 67,000 tonnes. In terms of area and production, plum (Prunus domestica) is Pakistan’s second largest stone fruit, after peach. Plum (Prunus domestica L.) is a temperate zone fruit crop, made up of different varieties. This study was carried out to evaluate the nutritional quality and yield performance of five different plum varieties (Methley, Shakar Prune, Santa Rosa, Hersminar, and Red Beaut) grown in the Punjab province of Pakistan. Plum samples were collected from the Horticultural Research Station, Nowshera (Soon Valley), Pakistan during May 2021 and analyzed for fruit yield and nutritional quality parameters. The maximum fruit fresh weight (52.9g) was recorded in Red Beaut and the lowest fresh weight (12.4 g) in Methley. The cultivar with the highest nutritional value was Shakar Prune with 16.4% of total soluble solids (TSS) and 12.2% of total sugars content, whereas the lowest nutritional value was recorded in Herisminar with total soluble solids (TSS) and total sugars content of 14.8% and 10.0%, respectively. All varieties showed significant variation in terms of fresh weight, total soluble solids (TSS), and total sugars. The results showed the yield performance and nutritional quality of different plum varieties, with Red Beaut and Shakarprune cultivars highlighted as the best. The study concluded that yield performance and nutritional quality depend strongly on the respective plum variety.